The Analysis Study of Safety and Outcome of Ureteroscopy During Pregnancy: A Comprehensive Systematic Review - Adzana Yasadhy Hangga Prasetyo; Yosie Yulanda Putra (International Medical Journal Corp. Ltd, 2024)
Background: Symptomatic urolithiasis in pregnancy can result in significant morbidity, causing conditions such as renal colic, urinary tract infections, and ureteral obstruction. This systematic review aim to analyze the safety and outcomes of uretrhoscopy for pregnant women. Methods: The study followed PRISMA 2020 guidelines, reviewing English-language publications from 2014 to 2024. Editorials, duplicate reviews from the same journal, and papers lacking a DOI were excluded. The literature search was conducted using PubMed, SagePub, SpringerLink, and Google Scholar. Result: A total of 2,172 articles were initially identified through online databases (PubMed, SagePub, SpringerLink, and Google Scholar). After three rounds of screening, eight relevant studies were selected for full-text analysis. Conclusion: Ureteroscopy is a safe, effective, and cost-efficient treatment for ureteral calculi during pregnancy. Early intervention minimizes complications, and URS remains a successful option for managing obstructive uropathy. Future research should optimize protocols and assess long-term outcomes for improved care.